2023
DOI: 10.1038/s43246-023-00401-3
|View full text |Cite|
|
Sign up to set email alerts
|

Operando tomographic microscopy during laser-based powder bed fusion of alumina

Malgorzata G. Makowska,
Fabrizio Verga,
Stefan Pfeiffer
et al.

Abstract: Laser-based Powder Bed Fusion (LPBF) of oxide ceramics enables fabrication of objects with complex three-dimensional shapes. However, mechanical properties of dense LPBF-manufactured ceramics are poor due to large amount of structural defects. Here, we perform the operando tomographic microscopy during LPBF of a magnetite-modified alumina to gain a deeper understanding of the underlying mechanisms. The effect of the laser energy density on the surface roughness, powder denudation zone and porosity formation me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 76 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…These adjustments prolonged the molten pool lifetime and decreased its viscosity due to elevated liquid temperature, facilitating gas bubble escape and porosity reduction. However, exceeding critical LED can be counterproductive, leading to an unstable molten pool or excessive material evaporation [190,194]. In addition to LED, other parameters such as scanning strategy, feedstock powder size, and substrate material also significantly impact porosity as demonstrated in [16,80,157].…”
Section: Pores Suppression Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These adjustments prolonged the molten pool lifetime and decreased its viscosity due to elevated liquid temperature, facilitating gas bubble escape and porosity reduction. However, exceeding critical LED can be counterproductive, leading to an unstable molten pool or excessive material evaporation [190,194]. In addition to LED, other parameters such as scanning strategy, feedstock powder size, and substrate material also significantly impact porosity as demonstrated in [16,80,157].…”
Section: Pores Suppression Methodsmentioning
confidence: 99%
“…Compared to other pore defects, LOF pores are less frequently reported in dAMed ceramics, likely attributed to their ease of avoidance through laser parameter tuning. For example, the studies on Al 2 O 3 and SiO 2 ceramics [107,190] reported cases of LOF defects between the deposited layer and substrate (figure 14(a)), which can be eliminated via either increasing laser power or reducing layer thickness. In contrast to the LOF defect, gas pores are originated from entrapped gas in the ceramic melt, and display a spherical or ellipsoidal shape with a smooth inner wall as shown in figure 14(b).…”
Section: Pores Formation Mechanismmentioning
confidence: 99%
See 2 more Smart Citations